Mechanosignaling-related angiocrine factors drive osteoblastic phenotype in response to zirconia - Fernandes, Célio Junior da C. [UNESP]; de Almeida, Gerson Santos [UNESP]; Wood, Patrícia Fretes [UNESP]; Gomes, Anderson M. [UNESP]; Bezerra, Fábio J. [UNESP]; Vieira, José C.S. [UNESP]; Padilha, Pedro M. [UNESP]; Zambuzzi, Willian F. [UNESP] (Elsevier, 2024)
Background: The growing use of zirconia as a ceramic material in dentistry is attributed to its biocompatibility, mechanical properties, esthetic appearance, and reduced bacterial adhesion. These favorable properties make ceramic materials a viable alternative to commonly used titanium alloys. Mimicking the physiological properties of blood flow, particularly the mechanosignaling in endothelial cells (ECs), is crucial for enhancing our understanding of their role in the response to zirconia exposure. Methods: In this study, EC cultures were subjected to shear stress while being exposed to zirconia for up to 3 days. The conditioned medium obtained from these cultures was then used to expose osteoblasts for a duration of 7 days. To investigate the effects of zirconia on osteoblasts, we examined the expression of genes associated with osteoblast differentiation, including Runx2, Osterix, bone sialoprotein, and osteocalcin genes. Additionally, we assessed the impact of mechanosignaling-related angiocrine factors on extracellular matrix (ECM) remodeling by measuring the activities of matrix metalloproteinases 2 and 9 (MMP2 and MMP9) during the acquisition of the osteogenic phenotype, which precedes mineralization. Results: Our data revealed that mechanosignaling-related angiocrine factors play a crucial role in promoting an osteoblastic phenotype in response to zirconia exposure. Specifically, exposed osteoblasts exhibited significantly higher expression levels of genes associated with osteoblast differentiation, such as Runx2, Osterix, bone sialoprotein, and osteocalcin genes. Furthermore, the activities of MMP2 and MMP9, which are involved in ECM remodeling, were modulated by mechanosignaling-related angiocrine factors. This modulation is likely an initial event preceding the mineralization phase. Conclusion: Based on our findings, we propose that mechanosignaling drives the release of angiocrine factors capable of modulating the osteogenic phenotype at the biointerface with zirconia. This process creates a microenvironment that promotes wound healing and osseointegration. Moreover, these results highlight the importance of considering the mechanosignaling of endothelial cells in the modulation of bone healing and osseointegration in the context of blood vessel effects. Our data provide new insights and open avenues for further investigation into the influence of mechanosignaling on bone healing and the osseointegration of dental devices.
Keywords: Biocompatibility; Biomaterial; Bone; Dental material; Endothelial cell; Mechanosignaling; Osteoblast; Zirconia